2013
DOI: 10.1097/shk.0b013e3182a676321
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-27 as a Sepsis Diagnostic Biomarker in Critically Ill Adults

Abstract: Purpose-We previously identified interleukin-27 (IL-27) as a sepsis diagnostic biomarker in critically ill children. The current study tested the performance of IL-27 alone and in combination with PCT for diagnosing sepsis in critically ill adults.Methods-Serum samples were made available from a prior prospective study of sepsis biomarkers in critically ill adults. The primary analysis used receiver operating characteristic (ROC) curves to evaluate the performance of IL-27 and PCT. Secondary analysis explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 11 publications
1
30
1
Order By: Relevance
“…However, in the secondary analysis a decision tree incorporating rules based on IL-27, PCT, and age reasonably estimated the risk of sepsis in subjects with a non-pulmonary source of sepsis, which is consistent with our previous study in critically ill adults (14). Previous biomarker studies have also demonstrated differences in biomarker performance depending on the source of infection (15), but the biological basis of the discrepancy in the performance of IL-27 between non-pulmonary versus pulmonary causes of sepsis is not evident.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, in the secondary analysis a decision tree incorporating rules based on IL-27, PCT, and age reasonably estimated the risk of sepsis in subjects with a non-pulmonary source of sepsis, which is consistent with our previous study in critically ill adults (14). Previous biomarker studies have also demonstrated differences in biomarker performance depending on the source of infection (15), but the biological basis of the discrepancy in the performance of IL-27 between non-pulmonary versus pulmonary causes of sepsis is not evident.…”
Section: Discussionsupporting
confidence: 89%
“…Based on our prior findings that the performance of IL-27 in adult patients may vary based on the source of sepsis (14), we then analyzed the performance of IL-27 in patients stratified by pulmonary versus non-pulmonary sepsis. Median plasma IL-27 concentrations were higher in the subjects with a non-pulmonary source of sepsis, compared to subjects without sepsis and subjects with a pulmonary source of sepsis (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations